PROBLEMATIKA PENERAPAN ASAS KEWAJARAN DALAM PENYELESAIAN SENGKETA TATA USAHA NEGARA - Izzati, Hafizah Nurul; Gayatri, Novalin Amanda; Wulandari, Wulandari (Faculty of Law, Universitas Tanjungpura, 2025)
Abstract This research aims to analyze the role and utilization of the principle of reasonableness in the settlement of state administrative disputes, as well as identify inhibiting factors and implementative solutions. Using a normative juridical method with a case study approach, data is obtained through literature study of legal literature and relevant laws and regulations. Data analysis techniques refer to the Miles and Huberman model: reduction, presentation, and conclusion drawing. The results show that the principle of reasonableness functions as a balancing instrument between formal legality and substantive justice in state administrative decisions. The urgency of this discussion lies in the lack of consistency in the application of the principle of reasonableness at the judicial level, which has the potential to perpetuate the abuse of administrative authority. The novelty of this paper lies in the systematic mapping of internal and external inhibiting factors in the application of the principle, as well as the preparation of recommendations based on jurisprudential decisions. The findings show that consistent application of the principle of reasonableness not only prevents malpractice of power, but also strengthens the moral legitimacy of the state administrative law system and increases public trust in the judicial process. bstrak Penelitian ini bertujuan untuk menganalisis peran dan pemanfaatan asas kewajaran dalam penyelesaian sengketa tata usaha negara, serta mengidentifikasi faktor-faktor penghambat dan solusi implementatifnya. Menggunakan metode yuridis normatif dengan pendekatan studi kasus, data diperoleh melalui studi pustaka dari literatur hukum dan peraturan perundang-undangan yang relevan. Teknik analisis data mengacu pada model Miles dan Huberman: reduksi, penyajian, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa asas kewajaran berfungsi sebagai instrumen pengimbang antara legalitas formal dan keadilan substantif dalam putusan tata usaha negara. Urgensi pembahasan ini terletak pada lemahnya konsistensi penerapan asas kewajaran di tingkat pengadiilan, yang berpotensi melanggengkan penyalahgunaan kewenangan administratif. Kebaruan tulisan ini terletak pada pemetaan sistematis faktor penghambat internal dan eksternal dalam penerapan asas tersebut, serta penyusunan rekomendasi berbasis putusan yurisprudensi. Temuan ini menunjukkan bahwa penerapan asas kewajaran yang konsisten tidak hanya mencegah malpraktik kekuasaan, tetapi juga memperkuat legitimasi moral sistem hukum administrasi negara dan meningkatkan kepercayaan publik terhadap proses peradilan.